Delimitation of a novel member of genus Metarhizium (Clavicipitaceae) by phylogenetic and network analysis - Chu, Hua-Li; Chen, Wan-Hao; Wen, Ting-Chi; Liang, Zong-Qi; Zheng, Fu-Chong; Liang, Jian-Dong; Han, Yan-Feng (Phytotaxa, 2016)
An entomopathogenic taxon from a wetland area in Guiyang City, China was found to be a novel species of Metarhizium based on both morphology and phylogeny. The new species, which has unique, slender and cylindrical, Akanthomyces-like synnemata is described, illustrated and named Metarhizium synnematis. Phylogenetic analysis of ITS sequence data confirmed that M. synnematis belongs in Metarhizium. It differs from other species of Metarhizium in having relatively small, ellipsoidal to cylindrical or sub-clavate conidia, coated with a thin mucilaginous sheath which aggregates spores into sticky masses.